Restoring Purpose in Behavior - Yin, Henry (Computational and Robotic Models of the Hierarchical Organization of Behavior, 2013)
The dominant paradigm in the study of behavior today is the linear causation paradigm. This paradigm, inspired by classical physics, assumes that causes precede effects, that the behavior of organisms is caused by antecedent events inside and outside the organism, and that future states such as goals and purposes cannot possibly cause behavior. It is the basis of the general linear model in psychology and the input/output analysis in neuroscience. But linear causation does not apply to any control system with negative feedback. Here I shall argue that organisms are collections of such negative feedback systems that control their perceptual inputs. The chief difference between the behavior of living organisms and that of non-living things is the presence of control. Rather than the effect of some prior cause, behavior is the observable manifestation of control in teleological systems that act on the environment to make inputs match their internal reference values. The previous rejection of control theory in the behavioral sciences was largely based on a misunderstanding of the principles of negative feedback control. I discuss the types of behavioral control enabled by the hierarchical organization and the experimental method for testing the controlled variable.